Pembelajaran SKI Melalui Google Sites - Puadi, Hairul; Madarik, Muhammad (LP3M Universitas Al-Qolam Malang, 2023)
In fact, the SKI (Islamic Cultural History) subject is somewhat shunned by most students. They viewed that SKI is a subject in the form of a set of